El art. 51 numeral 1 y 3 de las contrataciones de menor cuantía de bienes y servicios establecido en la ley orgánica del sistema nacional de contratación pública permite la elusión de procedimientos dinámicos lo que genera inconformidad jurídica en los oferentes ya que admite direccionar procesos - Moreno García, Karina Viviana (2015)
Public procurement in our country reborn as such from the enactment of the Organic Law of the National System of Public Procurement and Regulation, in all proceedings established by this standard is the Least Amount of Goods and Services a procedure that establishes its rules fairly guidelines for implementation and execution but despite that is increasingly used for the acquisition of goods and services, especially for STANDARD only in the event that the electronic reverse auction has been unsuccessful and when the amount for procurement is less than 0.000002 initial state budget for the financial period. From this perspective the most used I can express several discretionary aspects that the law allows, among which we can express: Contracting with the supplier is made directly, arguing that as already existed a dynamic process in this case the Reverse Auction Electronics, and how the process was declared void due to circumstances then there is justification that the law protects it to hire with any provider that meets the requirements of the law itself directly. This situation is worrying because the LOSNCP within its regulations establish the fundamental principles on which public procurement as the legality, transparency, equality and govern others. Then with the process established in the LOSNCP and the General Regulation, it goes against all these principles and to the competent administrative authority has absolute discretion to omit requirements and address these procedures, so it is necessary and urgent to establish a proposal reform in order to establish that all instances with this dynamic procedure, in order that the fundamental principles of public procurement are respected and the passage is closed and the opportunists who still entrenched corruption in the public service are exhausted . This study involves the analysis of the mechanisms for entities to make possible this type of procedure and carry out the various recruitment processes these without being outside the law, are exempt from certain formalities and requirements. In addition, this work is focused on determining the importance of the principles of legality, transparency and equality; in this way does not create legal nonconformity in other suppliers who feel the same right to such participation and for this you have to find the best means to be used for the existence of an effective internal and external control.